1997
DOI: 10.1136/gut.41.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase as the autoantigen of coeliac disease

Abstract: Three cases of apparent primary villous atrophy of the terminal ileum in women with chronic diarrhoea are reported. Eight cases have previously been reported in the literature. Clinical characteristics are the presence of severe chronic secretory diarrhoea with episodes of hypokalaemia combined with signs of ileal malabsorption and/or eYcacy of cholestyramine. Diagnosis is based on ileoscopy and histology. An association with microscopic colitis was present in the three patients and in four cases in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In fact, this widely used ELISA is based on tTG which is a crude extract from guinea pig liver; it has been verified that Sigma tTG is composed of at least 14 different components23 and it is logical to hypothesise that in the sera of patients with chronic liver disease there could be antibodies for protein antigens from the liver matrix, probably common (or cross reacting) to humans and other mammals. In fact, in the second part of the study when we were able to test our sera for anti-tTG using a pure human recombinant tTG, we did not observe any false positive results: all 13 subjects with false positive anti-tTG values when evaluated with the ELISA based on tTG from guinea pig as antigen resulted in negative values with the new ELISA system.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this widely used ELISA is based on tTG which is a crude extract from guinea pig liver; it has been verified that Sigma tTG is composed of at least 14 different components23 and it is logical to hypothesise that in the sera of patients with chronic liver disease there could be antibodies for protein antigens from the liver matrix, probably common (or cross reacting) to humans and other mammals. In fact, in the second part of the study when we were able to test our sera for anti-tTG using a pure human recombinant tTG, we did not observe any false positive results: all 13 subjects with false positive anti-tTG values when evaluated with the ELISA based on tTG from guinea pig as antigen resulted in negative values with the new ELISA system.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also in agreement with the recent report of 49 patients with type 1 diabetes who were positive for anti-tTG antibodies, assayed by radiobinding assay with recombinant human t-TG, but negative for EmA [17]. Third, and in our opinion the most probable hypothesis, it is possible that the false positive anti-tTG results we observed depend on the nature of the antigen of the ELISA method we used; in fact, this test is based on tTG which is extracted from guinea pig liver and it must be remembered that Sigma tTG is composed of at least 14 different components [18]; thus, it is possible that in the sera of our patients there could be antibodies for protein antigens from the liver matrix, probably common to humans; in any case, it must be remembered that most of the gastroenterological studies published to date [2, 3, 4, 19]which reported a very high specificity of anti-tTG determination for CD diagnosis were performed with the same ELISA we used in the present study, based on tTG on guinea pig liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tissue transglutaminase (tTG) has been identified as the most important, if not the sole, antigen against which anti-endomysium antibodies are directed (1,2). tTG is a ubiquitous enzyme located in various cell types and implicated in cellular wound healing and apoptosis (3,4).…”
mentioning
confidence: 99%